Organizational belief, managerial vision, and international trade - Jaewon Jung (FIW - Research Centre International Economics, 2015)
In this paper, we develop a simple general-equilibrium trade model in which heterogeneous workers make an investment decision in acquiring advanced managerial skills and choose their optimal effort level based on their own individual organizational beliefs and CEO's managerial vision. In doing so, we show how trade liberalization and/or changes in managerial vision of CEO may lead to non-monotonic income changes within firms due to the interaction between workers' beliefs and CEO's managerial vision. Whether a stronger (or weaker) CEO's managerial vision benefits the firm or not depends on its extent relative to workers' overall beliefs, and may involve some winners and losers within firms.
Keywords: F16; F66; 330; organizational belief; managerial vision; organizational change; international trade